PÅ TVÆRS I EN POLARISERET VERDEN - Nour, Susanne (Tidsskriftet Antropologi, 1998)
Susanne Nour: Cutting across a Polarised World The article focusses on the experiences of a young Egyptian woman from one of the socalled “old” families. It deals with her difficulties situating herself in Egypt. The present polarisation of Western and Islamic values makes it very difficult for her to formulate a national identity in correspondence with the hegemonic identity discourse in Egypt today. On the basis of interviews made during fieldwork in Cairo, the article argues for distinetion between two different constructions of Egyptian national identity and discuss how they are conneceted with different social groups, with particular family backgrounds, as well as with different interpretations of islam.